Acoustic Panels Inspired by Nature - Bartłomiej Dariusz BORKOWSKI; Katarzyna SUDER-DEBSKA; Jerzy WICIAK; Anna Maria SZLACHTA (Archives of Acoustics)
The article presents the approach to the design process of acoustic panels based on the scientific research. This approach is based on combining the technical and the design competences to develop the innovative product value for the concept of acoustic panels. The article presents the concepts of two new acoustic panels – an absorbing and scattering panel and a panel reflecting sound waves. The first part of the article presents the starting point for the presented project – the acoustic research and the inspiration for both types of presented solutions. Next, the materials possible to use were discussed, which could reproduce the natural acoustic properties of the lava and glacier caves. The next part presents consecutive stages of the product development in a modern form, ensuring the expected acoustic properties. The last part of the article presents a fully functional solution and proposes further research and development directions.